2021
DOI: 10.1002/er.6529
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of machine learning and deep learning algorithms for hourly global/diffuse solar radiation predictions

Abstract: Summary Due to the advancement and wide adoption/application of solar‐based technologies, the prediction of solar irradiance has attracted research attention in recent years. In this study, the predictive performance of machine learning models is compared with that of deep learning models for both global solar radiation (GSR) and diffuse solar radiation (DSR) prediction. Different studies have proposed the use of different models for solar radiation prediction. While some used machine learning models, the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Based on a comparison between the predictive model and the actual WHR simulated cycle, it can be concluded that data science can be used as an alternative to thermodynamic modelling to avoid time‐consuming calculations. Comparing machine learning and deep learning algorithms for estimating hourly global/diffuse solar radiation, Bamisile et al 8 found that all deep learning models produced in this work performed better than machine learning models. Cheng and Yu 9 discussed machine learning technologies applied to smart energy and electric power systems, beginning with an introduction to seven types of machine learning (ML) methods and systematically reviewing their applications in Smart energy and electric power system (EEPS), and concluding with a discussion of ML development under the big data thinking and a future development outlook for AI 2.0 and ML in Smart EEPS, etc.…”
Section: Introductionmentioning
confidence: 81%
“…Based on a comparison between the predictive model and the actual WHR simulated cycle, it can be concluded that data science can be used as an alternative to thermodynamic modelling to avoid time‐consuming calculations. Comparing machine learning and deep learning algorithms for estimating hourly global/diffuse solar radiation, Bamisile et al 8 found that all deep learning models produced in this work performed better than machine learning models. Cheng and Yu 9 discussed machine learning technologies applied to smart energy and electric power systems, beginning with an introduction to seven types of machine learning (ML) methods and systematically reviewing their applications in Smart energy and electric power system (EEPS), and concluding with a discussion of ML development under the big data thinking and a future development outlook for AI 2.0 and ML in Smart EEPS, etc.…”
Section: Introductionmentioning
confidence: 81%
“…Deep learning is a subfield of machine learning, and ANNs form the backbone of deep learning algorithms. In fact, the distinguishing feature of a single ANN from the deep learning algorithm is the number of node layers or the depth of the neural networks, which must be more than three in the deep learning algorithm [35]. In this article, the CNN-LSTM algorithm is used.…”
Section: Methodsmentioning
confidence: 99%
“…The expansion of solar energy-based technologies and applications will continue 40 . Therefore, the reliable estimation of solar radiation including its hourly, daily average, monthly average, annual, 41 and seasonal variability is of paramount importance for the estimation of solar energy capacity and potential 42 . As mentioned earlier, the high cost and technological complexity attached to the measurement of solar radiation makes it a more difficult task in many meteorological stations.…”
Section: Introductionmentioning
confidence: 99%